The dynamical characteristics of a multi-purpose tracked vehicles under various schemes of hydraulic shock absorbers suspension - D. A. Skripnichenko (Вестник СибАДИ)
Held on the training ground and experimental studies of dynamic characteristics of multi-purpose tracked vehicles under various schemes of hydraulic shock absorbers suspension in different conditions of movement in the terrain is defined as hydraulic shock absorbers and without them. The levels of influence of hydraulic shock absorbers on the dynamic characteristics of multi-purpose tracked vehicles. A comparison of the results of the kinematic excitation of the undercarriage when driving on rough terrain with absorbers and without them.